(untitled) (Agora for Physical Education and Sport, 2020)
The use of didactic material could be an important help to include students with special educational needs in Physical Education mainstream classes. The aim of this paper is to know the opinions regarding the use of recycled material with the aim of attending the diversity in Physical Education of a group of 145 pre-service Early-childhood and Primary-Education teachers. First, a scale was built for this purpose, which obtained adequate reliability and validity results. Second, the results were compared according to gender and grade, without obtaining significant differences. Lastly, a group of 26 pre-service teachers participated in an experience of construction-recycled material and its implementation with a group of people with intellectual impairments. Participants significantly improved their opinions after the intervention. It is concluded that the instrument were valid and reliable for the evaluation of opinions towards the use of recycled material for the attention of students with disabilities in Physical Education and that the construction and use of the material improve this opinion in pre-service teachers.